Introduction to Cosmology - Roos, Matts (New York Academy of Sciences Ser., 2015)
Matts Roos is Emeritus Professor in Particle Physics at the University of Helsinki, Physics Department, where he is still active in research and postgraduate teaching. Roos is a member of the Finnish Physical Society, honorary member of The Physical Society in Finland, and founding member of the Particle Data Group which produces the biannual compilation published as Review of Particle Physics. He is also a member of the International Astronomical Union, the Steering Committee of the COSMO conferences, and a honorary member of the Japan Society for the Promotion of Science, Finnish Alumni Club. -- Provided by publisher.